Address by Mr Koïchiro Matsuura, Director-General of UNESCO, on the occasion of the ceremony of the first stone laying of the International Olonkho Centre; Yakutsk, Republic of Sakha (Yakutia), Russia, 24 July 2006 - UNESCO. Director-General, 1999-2009 (Matsuura, K.) (24 July 2006, 2006)
Electronic version only